2021
DOI: 10.3390/biom11071025
|View full text |Cite
|
Sign up to set email alerts
|

The Demethoxy Derivatives of Curcumin Exhibit Greater Differentiation Suppression in 3T3-L1 Adipocytes Than Curcumin: A Mechanistic Study of Adipogenesis and Molecular Docking

Abstract: Curcumin is a known anti-adipogenic agent for alleviating obesity and related disorders. Comprehensive comparisons of the anti-adipogenic activity of curcumin with other curcuminoids is minimal. This study compared adipogenesis inhibition with curcumin, demethoxycurcumin (DMC), and bisdemethoxycurcumin (BDMC), and their underlying mechanisms. We differentiated 3T3-L1 cells in the presence of curcuminoids, to determine lipid accumulation and triglyceride (TG) production. The expression of adipogenic transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…This is speculated to result from the structural similarity shared by curcumin and its derivatives. One study suggested that curcumin analogs interact with PPARγ to suppress adipogenesis more effectively than curcumin [ 73 ]. This implies that derivatives of curcumin may outperform curcumin in targeting the PPARγ isoform regulating adipogenesis, while activating the PPARγ isoform associated with inflammation and lipid metabolism suppression.…”
Section: Discussionmentioning
confidence: 99%
“…This is speculated to result from the structural similarity shared by curcumin and its derivatives. One study suggested that curcumin analogs interact with PPARγ to suppress adipogenesis more effectively than curcumin [ 73 ]. This implies that derivatives of curcumin may outperform curcumin in targeting the PPARγ isoform regulating adipogenesis, while activating the PPARγ isoform associated with inflammation and lipid metabolism suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the proposed mechanism for the reduction of triglyceride levels after curcumin supplementation is that curcuminoids promote down‐regulation of peroxisome proliferator‐activated receptor γ expression (PPARγ) and CCAAT/enhancer‐binding protein α (C/EBPα), leading to the reduction of acetyl‐CoA carboxylase and fatty acid synthase enzymes (Alalaiwe et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…(C/EBPα), leading to the reduction of acetyl-CoA carboxylase and fatty acid synthase enzymes (Alalaiwe et al, 2021).…”
Section: F I G U R Ementioning
confidence: 99%
“…α-Tocopherol, LA, or CLA (1‒500 µM) in free and nanoparticulate forms were added to the wells for a 24-h treatment. Then, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) at 0.5 mg/ml was added to the wells for 2 h. The other procedures were the same as previously reported [ 20 ].…”
Section: Methodsmentioning
confidence: 99%